A qualitative study exploring the experience of viewing three‐dimensional medical images during an orthopaedic outpatient consultation from the perspective of patients, health care professionals, and lay representatives. Issue 2 (2nd June 2020) - Phelps, Emma E.; Wellings, Richard; Kunar, Melina; Hutchinson, Charles; Griffiths, Frances
Abstract: Rationale, aims and objectives: Three‐dimensional (3D) medical images are shown to patients during clinical consultations about certain health conditions. However, little is known about patients' experience of viewing them. The aim of this qualitative study was to explore the impact of sharing 3D medical images with patients during a clinical consultation about hip surgery, from the perspective of patients, health care professionals, and lay representatives. Method: Interviews were conducted with 14 patients who were shown their own 3D medical images during their clinical consultation and four health care professionals conducting consultations within one orthopaedic outpatient clinic. In addition to interviews, 31 lay representatives participated in six focus groups. The focus groups aimed to gain a broader understanding of the advantages and concerns of showing patients their medical images and to compare 3D and two‐dimensional (2D) medical images. Interviews and focus groups were audio‐recorded, transcribed verbatim, and analysed using thematic analysis. Results: Three themes were developed from the data: (a) the truthful image, (b) the empowering image, and (c) the unhelpful image. Focus group participants' preference for 3D or 2D images varied between conditions and groups, suggesting that the experience of viewing images may differ between individuals and conditions. Conclusions: When shown to patients during an orthopaedic clinical consultation, 3D medical images may be an empowering resource. However, in this study, patients and focus group participants perceived medical images as factual and believed they could provide evidence of a diagnoses. This perception could result in overreliance in imaging tests or disregard for other forms of information.